Improvement Of Reading Comprehension Skills Through the Exelearning.Net Interactive Model in Upper Basic Students - Beltrán Ponce, Carmen Miryam (2024)
The purpose of this study was to investigate the impact of the interactive model known as "Exelearning.net" on improving reading comprehension skills among students of Basic Superior in Santa Elena, Ecuador. An experimental study with a quantitative approach was conducted, involving a sample of 70 students divided into two groups of 35. Pre and post-tests were administered to assess reading comprehension. Statistical analyses revealed significant improvements in the dimensions of literal, inferential, and critical comprehension, with higher scores in the experimental group than in the control group. The results showed a significance level of < 0.001, indicating that the application of the interactive model ExeLearning.net had a positive impact on strengthening students' reading comprehension skills. These findings suggest that using interactive programs can facilitate the relationship between reading and text comprehension.